Evaluation of combustion, performance, and emissions of optimum palm-coconut blend in turbocharged and non-turbocharged conditions of a diesel engine - Arbab, M.I.; Varman, M.; Masjuki, Haji Hassan; Kalam, Md. Abul; Imtenan, S.; Sajjad, H.; Fattah, I.M.R. (Elsevier, 2015)
Fossil fuel depletion, global warming with rapid changes in climate, and increases in oil prices have motivated scientists to search for alternative fuel. Biodiesel can be an effective solution despite some limitations, such as poor fuel properties and engine performance. From this perspective, experiments were carried out to improve fuel properties and engine performance by using a binary blend of palm and coconut biodiesel at an optimized ratio. MATLAB optimization tool was used to determine this blend ratio. A new biodiesel was developed and represented by PC (optimum blend of palm and coconut biodiesel). Engine performance and emission were tested under a full load at variable speed condition by using a 20 blend of each biodiesel with petroleum diesel, and the results were compared with petroleum diesel under both turbocharged and non-turbocharged conditions. PC20 (blend of 20 PC biodiesel and 80 petroleum diesel) showed the highest engine power with lower brake-specific fuel consumption than the other tested fuels in the presence of a turbocharger. The emissions of PC20 were lower than those of all other tested fuels. The experimental analysis reveals that PC showed superior performance and emission over palm biodiesel blend. (C) 2014 Elsevier Ltd. All rights reserved.